Social, Environmental and Political dimensions of Roots Crop Value Chain Analysis: The Case of Samar, Philippines - Joy Araza (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper evaluates the Social, Environmental and Political dimensions of Roots Crop Value Chain Analysis in the Case of Samar, Philippines through crop accounting and financial analysis in 2nd district, Western Samar, Philippines. Commercially important crops in Samar are the roots crops that the local farmer are producing for commercial and for personal consummations such as banana, sweet potato, cassava, yam and taro, locally known as “saging na analdaba, kamote, bilanghoy, ube and gaway”respectively, are well-known for their ability to produce a reasonable yield in poor soil conditions with less or no farm inputs. This is the reason why these commercially important crops are often grown by resource-limited farmers and are regarded as a good source of food security and its health benefit. To analyze its productivity, this study was conducted in 2022. Data gathering was primarily done through survey questionnaire, researcher observation and key informant interviews. Results revealed that different gender roles exist where men are primarily responsible for farming while women are for marketing. It also discovered the reason why farmers, though provided with options, often choose the less profitable transaction path, due to perishability of crop. It also solved the mystery of low productivity in this locale as compared with the national and international production. Typhoons, government policies, and pricing mechanisms affect its overall productivity. Cost build-up, value-added, and cost and returns analyses are interesting. Farmers are less profitable yet have the highest opportunity for profitability when the constraints are addressed while sellers have a high degree of profitability due to fewer input costs. The existing entry barriers in each chain were also identified, along with the researcher’s recommendations on how to eliminate or mitigate them.